2007
DOI: 10.1108/s1548-6435(2007)0000003006
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Marketing Research on Diffusion of New Products

Abstract: We critically examine alternate models of the diffusion of new products and the turning points of the diffusion curve. On each of these topics, we focus on the drivers, specifications, and estimation methods researched in the literature. We discover important generalizations about the shape, parameters, and turning points of the diffusion curve and the characteristics of diffusion across early stages of the product life cycle. We point out directions for future research.Because new products affect every aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 133 publications
(220 reference statements)
2
76
0
3
Order By: Relevance
“…Because of this high variation, the point of chasm would vary by product category, though it is likely to be the same across countries. Indeed, prior research has shown that diffusion parameters are unique to particular products (e.g., Chandrasekaran and Tellis 2007;Muller and Yogev 2006). Therefore, for each product, a mean penetration level that reflects early market adoption and late market nonadoption can serve as a proxy for the location of the chasm.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this high variation, the point of chasm would vary by product category, though it is likely to be the same across countries. Indeed, prior research has shown that diffusion parameters are unique to particular products (e.g., Chandrasekaran and Tellis 2007;Muller and Yogev 2006). Therefore, for each product, a mean penetration level that reflects early market adoption and late market nonadoption can serve as a proxy for the location of the chasm.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, studies have introduced and validated a new metric to measure how quickly a market adopts a new product,i.e., the takeoff of new products (see Agarwal and Bayus 2002, Chandrasekaran and Tellis 2007, Golder and Tellis 1997, Tellis et al 2003. Takeoff marks the turning point between introduction and growth stages of the product life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…These models do not try to explain why individual decisions are taken within the population. In the pioneering studies of diffusion the use of the logistic equation [2,9] can be seen as a special case of the Bass model [10] which, in turn, is a particular case of models based on the gamma/shifted Gompertz distribution [7]. Moreover, epidemiologic models are similar to population models [5].…”
Section: How This New Approach To the Diffusion Of Technology Innovatmentioning
confidence: 99%
“…The initial studies (and a good share of the publications) about diffusion of innovations have taken place in the field of agriculture [3]. More recent references [4][5][6][7] provide literature reviews concerning theories of diffusion models. Historically, there have been two major approaches to the diffusion of innovations; those trying to reproduce the patterns of diffusion [8] and those trying to understand the underlying factors that affect decision-making mechanisms determining the market roll-out of innovations.…”
Section: How This New Approach To the Diffusion Of Technology Innovatmentioning
confidence: 99%